PENGGUNAAN METODE PEMBELAJARAN FIELD TRIP UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA PGSD PADA MATA KULIAH PENDIDIKAN IPA KELAS TINGGI - Br Tarigan, Rupina Magdalena (Jurnal Tematik, 2019)
This study aims to know the use of Field Trip learning methods to improve student learning outcomes in High Class Science courses. This type of research is Class Action Research. The results of the study show that in the first cycle data obtained from student learning outcomes in a classical still low, namely from 31 students there were only 3 people (9.68%) with very good learning outcomes, and 5 people (16.13%) with categories good, 12 people (38.71%) in sufficient categories, while student learning outcomes in the category of less than 11 people (35.48%). Then after the second cycle, with the application of the Field Trip learning method student learning outcomes increased to 6 people (19.35%) with very good learning outcomes, 17 people (54.84%) with good categories, whereas with the category there were only 7 people (22.58%), but there is still one person (3.23%) whose learning outcomes are still relatively poor. Based on the results of testing hypotheses conducted by the researcher, conclusions were obtained by using the Field Trip learning method that could improve the learning outcomes of primary education students in the Quality University in the High Class Science Education course.